AMPK signaling and its targeting in cancer progression and treatment. (October 2022) - Hsu, Che-Chia; Peng, Danni; Cai, Zhen; Lin, Hui-Kuan
Abstract: The intrinsic mechanisms sensing the imbalance of energy in cells are pivotal for cell survival under various environmental insults. AMP-activated protein kinase (AMPK) serves as a central guardian maintaining energy homeostasis by orchestrating diverse cellular processes, such as lipogenesis, glycolysis, TCA cycle, cell cycle progression and mitochondrial dynamics. Given that AMPK plays an essential role in the maintenance of energy balance and metabolism, managing AMPK activation is considered as a promising strategy for the treatment of metabolic disorders such as type 2 diabetes and obesity. Since AMPK has been attributed to aberrant activation of metabolic pathways, mitochondrial dynamics and functions, and epigenetic regulation, which are hallmarks of cancer, targeting AMPK may open up a new avenue for cancer therapies. Although AMPK is previously thought to be involved in tumor suppression, several recent studies have unraveled its tumor promoting activity. The double-edged sword characteristics for AMPK as a tumor suppressor or an oncogene are determined by distinct cellular contexts. In this review, we will summarize recent progress in dissecting the upstream regulators and downstream effectors for AMPK, discuss the distinct roles of AMPK in cancer regulation and finally offer potential strategies with AMPK targeting in cancer therapy.